One-dimensional modeling of heterogeneous catalytic chemical looping steam methane reforming in an adiabatic packed bed reactor - Qayyum, Haris; Cheema, Izzat Iqbal; Abdullah, Mohsin; Amin, Muhammad; Khan, Imtiaz Afzal; Lee, Eui-Jong; Lee, Kang Hoon (Frontiers in Chemistry, 2023)
Hydrogen production by using chemical looping steam methane reforming (CL-SMR) is one of the most promising technology. This work presents the development of 1-D model of adiabatic packed bed reactor used for chemical looping reforming (CLR) in gPROMS model builder 4.1.0 ® . Catalyst used for this process was 18 wt. % NiO with the support of Al2O3. A brief thermodynamic analysis using Chemical Equilibrium Application (CEA) is done to find optimum operating condition. The model is simulated for 10 complete CL-SMR cycles. The effects of temperature, pressure, gas mass velocity, Nickel Oxide concentration, reactor length and particle diameter are studied to check the performance of CL-SMR process. A parametric analysis was carried out for different range of conditions: temperature from 600 to 1000 K, pressure from 1 to 5 bar, gas mass velocity between 0.5 and 0.9 kg m -2 s -1 , Nickel oxide concentration between 0.1 and 1 mol m -3 , particle diameter between range of 0.7 and 1 mm and fuel reactor (FR) length between 0.5 and 1.5m. At optimum temperature (950 K), Pressure (1 bar) and steam-to-carbon molar ratio (3/1), with the increase in the particle diameter from 0.7 to 1 mm, 18 % decrease in methane conversion and 9.5 % increase in hydrogen yield were observed. Similarly, with increase in FR length from 0.5m to 1.5m delay in temperature drop was observed.